Synthesis and catalytic application of silver nanoparticles supported on lactobacillus Kefiri S-Layer proteins - Bolla, Patricia Araceli (2020)
Research on nanoparticles obtained on biological supports is a topic of growing interest in nanoscience, especially regarding catalytic applications. Silver nanoparticles (AgNPs) have been studied due to their low toxicity, but they tend to aggregation, oxidation, and low stability. In this work, we synthesized and characterized AgNPs supported on S-layer proteins (SLPs) as bidimensional regularly arranged biotemplates. By different reduction strategies, six AgNPs of variable sizes were obtained on two different SLPs. Transmission electron microscopy (TEM) images showed that SLPs are mostly decorated by evenly distributed AgNPs; however, a drastic reduction by NaBH4 led to large AgNPs whereas a smooth reduction with H2 or H2 /NaBH4 at low concentration leads to smaller AgNPs, regardless of the SLP used as support. All the nanosystems showed conversion values between 75–80% of p-nitrophenol to p-aminophenol, however, the increment in the AgNPs size led to a great decrease in Kapp showing the influence of reduction strategy in the performance of the catalysts. Density functional theory (DFT) calculations indicated that the adsorption of p-nitrophenolate species through the nitro group is the most favored mechanism, leading to p-aminophenol as the only feasible product of the reaction, which was corroborated experimentally.